Pengaruh Profitabilitas, Ukuran Perusahaan, Leverage, Dan Likuiditas Terhadap Nilai Perusahaan (Studi Perusahaan Property Dan Real Estate Tahun 2018-2022) - Julietta Fariskha Risaani; Sri Sudarsi (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
The company’s value is evidence that the entity has tried to run the company’s operation well with maximum profit and is a useful indicator for investors and shareholders, as it describes the success of an entity that can be seen from the price of shares. From that understanding it was decided to testing and proving the significance of profitability (ROE), company size (SIZE), leverage (DER), and liquidity (CR) towards company’s value (PBV). This type of research is the entire property and real estate companies listed on the Indonesian Stock Exchange (IDX) and sampling using purposive sampling with the final sample of 90 surveys. Double linear regression for data analysis methods using the help of SPSS software. From this study obtained results and proved that profitability (ROE) and leverage (DER) have an influence towards company’s value. Whereas, company’s size (SIZE) and liquidity (CR) proved to have no influence towards company’s value.